Tinjauan Yuridis Terhadap Penerapan Prinsip Kehati-Hatian oleh Bank dalam Memberikan Kredit - Montayana Meher (Mahesa Research Center, 2023)
The activity of channeling funds through credit occupies the most important position, because it provides the greatest profit and opinion. The profit comes from credit interest which is commonly called fee-based income, therefore in lending must be carried out with the principle of prudence through accurate and in-depth analysis. The research in writing this scientific work is normative juridical research. Normative juridical research is research that examines the application of legal rules and norms related to the topic discussed. The nature of this research is descriptive, namely research that analyzes a legal regulation. The process of implementing credit to customers is carried out in a way: File Submission, Investigation of former loans, Interview I, On The Spot, Interview II, Credit Decision, Signing of credit contracts / other agreements, Credit Realization, Distribution / withdrawal. In applying the prudential principle in providing credit, banks can analyze the data and character of prospective customers by applying the 5P principle and the 5C principle. The process of resolving disputes between banks and customers in the event of bad credit can be done through non-litigation channels, which are out-of-court settlements and through litigation channels, which are the last resort of banks to make efforts to recover debtor credit either by executing credit collateral, taking over credit collateral by banks or by filing a lawsuit in the District Court.